Binge Watching on Generation Z FOMO with Emotionally Immature Parents: Binge Watching Terhadap FOMO Generasi Z Dengan Emotionally Immature Parents - Pradiansyah, Bunga Nadira; Fajar Islam, Azizah (Jurnal Ilmiah Penelitian Psikologi, 2024)
The expanding digital age has made consuming media easily accessible for those living in Indonesia. This ease of digitalization can also have negative consequences such as FOMO and Binge Watching, especially in Generation Z with emotionally immature parents. This can lead to technology addiction. This study aims to determine the effect of Binge Watching behavior on Fear of Missing Out in Gen Z with emotionally immature parents. Through a quantitative approach, this study uses non-probability sampling with purposive sampling technique involving 50 male and female respondents with an average age of 14-24 years; enjoy watching series/movies/drama more than 1 time without interruption; have unpleasant experiences with parents. Data were collected online through a questionnaire adapted from the Binge Watching Engagement and Symptoms Questionnaire developed by Flayelle et al. (2018) and the Online Fear of Missing Out Inventory developed by Sette (2019). The results of the linear regression test showed that the F-value of the two variables was 36.904 with an unstandardized B-value of 0.614 and a P-value of 0.05> 0.000. This shows that H0 is rejected in this study, so there is a significant influence between Binge Watching Behavior and Fear of Missing Out in Generation Z with Emotionally Immature Parents, which has a percentage of 43.5%.